Attorney Role In Fighting Crimes Of Motorcycle Gang In Cirebon - Asep Sunarsa (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Establishment of the motorcycle gang began with the gathering fellow motorcycle enthusiasts, which then turned into a gang of tens or even hundreds of people. Motorcycle gang shaping the lifestyle that sometimes deviate from the norm for the sake of self-adhesive group identity on the streets. The doctrine attached to each self motorcycle gang members were motivated to commit a crime that is very detrimental to the community. Motorcycle gang act according to the standpoint of law, especially criminal law, there are several actions against the law, in the community a lot of evidence that shows that often occurs offense aggravated theft with violence offenses that threaten the lives and physical person.Keywords: Role of Public Prosecution; Prevention; Criminal Law; Motorcycle gang.